Meeting Places in Space of Horror. Testimonial Approach to the Chilean Detention And/Or Torture Centers - Santos-Herceg, J (UNIV VALENCIA, DEPT PREHISTORIA & ARQUEOLOGIA, 2015)
This paper seeks to approach to the topic of thc resistance inside thc Chilean Detention and / or Torture Centers from the perspective of the places. It is argued that prisoners construct spaces which are linked positively and allow them to rmanta.in their humanity in the middle of horror. As examples, we study the spaces of communication, the places for love, and the sacred places inside this Colierv.